The role of GIPR in food intake control - James-Okoro, Paula-Peace; Lewis, Jo Edward; Gribble, Fiona Mary; Reimann, Frank (Frontiers in Endocrinology, 2025)
Glucose-dependent insulinotropic polypeptide (GIP) is one of two incretin hormones playing key roles in the control of food intake, nutrient assimilation, insulin secretion and whole-body metabolism. Recent pharmacological advances and clinical trials show that unimolecular co-agonists that target the receptors for the incretins – GIP and glucagon-like peptide 1 (GLP-1) – offer more effective treatment strategies for obesity and type 2 diabetes mellitus (T2D) compared with GLP-1 receptor (GLP1R) agonists alone, suggesting previously underappreciated roles of GIP in regulating food intake and body weight. The mechanisms by which GIP regulates energy balance remain controversial as both agonism and antagonism of the GIP receptor (GIPR) produce weight loss and improve metabolic outcomes in preclinical models. Recent studies have shown that GIPR signalling in the central nervous system (CNS), especially in regions of the brain that regulate energy balance, is essential for its action on appetite regulation. This finding has sparked interest in understanding the mechanisms by which GIP engages brain circuits to reduce food intake and body weight. In this review, we present key knowledge around the actions of GIP on food intake regulation and the potential mechanisms by which GIPR and GIPR/GLP1R agonists may regulate energy balance.